Allergy to beta-lactam antibiotics - Lao-araya, Mongkol (Biomedical Sciences and Clinical Medicine, 2024)
Beta-lactams are the most widely use antibiotics for treatment of bacterial infections. The reports of beta-lactam allergy are very common in clinical practices. In these patients, beta-lactams are commonly withheld due to fear of subsequent adverse reactions. Diagnosis of beta-lactam allergy based solely on the history without further investigation may affect treatment options, result in adverse consequences, lead to the use of more-expensive or less-effective drugs, and increase risk of developing resistant organisms. Up to 90% of patients claimed to be allergic to beta-lactam can tolerate after appropriate evaluation. The purpose of this review is to providing comprehensive evidences for practical management for evaluating beta-lactam allergy.